Health of street children in Cape Town, May-November 1989 - Gebers, Paul Eric (Department of Paediatrics and Child Health, 2018)
This cross-sectional study looks at the health profiles of street children both in institutions and on the street between May and November 1989. The former group had a clinical examination, with blood and urine investigations done where possible; the latter group were only interviewed. 159 street children were interviewed of whom 47 were interviewed on the street. 73 children had clinical examinations; 64 of these had blood and urine investigations. The age range was 8 years to 19.8 years. 18.2% were females and 28.3% were black. 59,6% of those interviewed on the street had not been in an institution or shelter for street children. 27, 2% of the total group had been on the street for more 3 years. 3 7, 1 % perceived colds and chest complaints as their main physical health problem. This was confirmed by the fact that 69,2% had a history of respiratory problems. 44,7% said that they would go to a hospital if they injured themselves or were ill; however, 36,5% said they would not use or get any medication for problems such as a headache or a bad cold. 37·, 7% of children used a hospital while they were on street but 59, 7% had not used any facility while on the street. Most street children (72,8%) washed themselves at least occasionally and 61% washed their clothes. 47,2% had suffered trauma significant enough to seek hospital attention. 56% had skin problems (including lice and scabies) while on the street. 15,7% complained of visual problems and 10,7% complained of reduced hearing. Dental problems appeared to be of major concern with 37,7% complaining of either toothache or dental caries (23,3% had obvious caries on examination). 73,4% admitted to solvent abuse, 49,9% had never taken alcohol and 12,7% had never smoked. 43% had tried dagga, 10,8% white pipe (mixture of dagga and "Mandrax" which is smoked) and only 7,6% "Mandrax" alone. 10, 9% of boys and 10, 0% of girls indicated that they had been sexually exploited. Of the 67 examined 32,8% were below 90% of expected height for age, 44,8% were below 80% of expected weight for age and 8,6% had a circumference of head below 95% of standard. There is a 9,4% Hepatitis Bs ag carrier rate. No HIV (human immunodeficiency virus) antibodies were detected in 64 sera tested. On the basis of these results, the following are recommended: 1) Improving accessibility of health care resources. 2) Improving the availability of health care resources. 3)· Initiating contacts with street children by employing field health workers. 4) Drawing up a health care policy for street children institutions and field care workers. 5) Limit venereal disease management to single dose treatment where possible. 6) Further studies need to be undertaken in the following areas: - solvent abuse - utilisation of health care resources utilisation institutions of street children shelters and Further breakdown of habits, physical problems and results of examinations are presented.